PPAR-γ, RXR, VDR, and COX-2 Expressions in gingival tissue samples of healthy individuals, periodontitis and peri-implantitis patients - Taskan, M; Gevrek, F (Nigerian journal of clinical practice, 2020)
Objective: Periodontitis and peri-implantitis are irreversible destructive diseases of periodontal and peri-implant tissues. This study aimed to determine the receptor expressions of peroxisome proliferative-activated receptor (PPAR)-γ, retinoid X receptor (RXR)-α, vitamin D receptor (VDR), and cyclooxygenase (COX)-2 in diseased tissues around teeth and dental implants. Subjects and Methods: The study consisted of three groups: group 1, healthy group (C, n = 15); group 2, periodontitis patients with stage 3 grade B (P, n = 15); and group 3, peri-implantitis patients (PI, n = 15). Periodontal clinical parameters such as the plaque index (PI), gingival index (GI), and probing pocket depths (PPD) were recorded. Gingival and peri-implant mucosal biopsies were obtained from all participants and biopsy samples underwent histological tissue processing. Hematoxylin-eosin (H & E) and immunohistochemistry staining were performed. Total inflammatory cell counts and fibroblast cell density were evaluated on H and E-stained slides, while PPAR-γ, RXR-α, VDR, and COX-2 were evaluated through immunohistochemistry. Results: The age of participants were similar, while PI, GI, and PPD values were higher in periodontitis and peri-implantitis groups compared with healthy group. Inflammatory cell infiltration was higher in periodontitis and peri-implantitis compared with healthy group, while fibroblast cell density exhibited a reverse pattern. PPAR-γ and also COX-2 expressions were lower in the healthy group and higher in periodontitis and peri-implantitis groups. RXR-α and VDR were higher in the healthy group and lower in the periodontitis and peri-implantitis groups. Conclusion: The results revealed that RXR-α and VDR levels were higher, while PPAR-γ and COX-2 levels were lower in the healthy group and periodontitis and peri-implantitis groups resulting in similar expressions in the tested parameters.